2015
DOI: 10.15288/jsad.76.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Cognitive Control Helps Explain Comorbidity Between Alcohol Use Disorder and Internalizing Disorders

Abstract: ABSTRACT. Objective: Alcohol use and internalizing problems frequently co-occur. Cognitive control has been implicated in their etiology, but no studies have tested whether this construct helps explain the co-occurrence of these disorders. Method: A total of 1,313 undergraduate students completed assessments of cognitive control, negative emotionality, and symptoms of alcohol use disorder (AUD), depression, and generalized anxiety disorder. Structural equation models examined the extent to which overlap betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…Therefore, despite differences in methodology between the study by Jonker and colleagues (2014) and the current study, results collectively highlight the importance of exploring the unique effects of inhibitory control as regulators between punishment sensitivity and substance use, particularly within an emerging adult population. We also note that, consistent with mixed findings from past research (e.g., Ellingson et al, 2015; Meehan et al, 2013; Wong & Rowland, 2013), the main effects of inhibitory control were rather small and inconsistent in predicting alcohol and marijuana use. Instead, we found that activation control showed consistent main effects on alcohol and marijuana use.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, despite differences in methodology between the study by Jonker and colleagues (2014) and the current study, results collectively highlight the importance of exploring the unique effects of inhibitory control as regulators between punishment sensitivity and substance use, particularly within an emerging adult population. We also note that, consistent with mixed findings from past research (e.g., Ellingson et al, 2015; Meehan et al, 2013; Wong & Rowland, 2013), the main effects of inhibitory control were rather small and inconsistent in predicting alcohol and marijuana use. Instead, we found that activation control showed consistent main effects on alcohol and marijuana use.…”
Section: Discussionsupporting
confidence: 88%
“…Most of the existing research examining the association between effortful control and substance use has examined only direct associations primarily based on self-report measures, and findings are mixed in emerging adult populations with some studies reporting modest associations ( r = .12 to .25; Ellingson, Richmond-Rakerd, & Slutske, 2015; Wong & Rowland, 2013) and others reporting no association ( r = −.04; Meehan et al, 2013). Despite the equivocal evidence supporting a direct association between effortful control components and substance use outcomes in emerging adult populations, the moderating effects of effortful control have not been extensively studied.…”
Section: Effortful Controlmentioning
confidence: 99%
“…Empirical work suggests mechanisms by which behavioral control may underlie both MDD and AUD, including attentional biases (Hankin et al 2010; Sharbanee et al 2014), delay discounting (Bickel & Marsch, 2001; Pulcu et al 2014), and effortful/inhibitory control (Field et al 2010; Kanske & Kotz, 2012). Consistent with this literature, prior work by our group has shown that trait effortful control (comprised of attentional, activational, and inhibitory control) explains phenotypic covariation between MDD and AUD, beyond what can be explained by negative emotionality (Ellingson et al 2015). Further, behavioral control fits within the RDoC cognitive system, which includes constructs related to attention, response selection, and response inhibition.…”
Section: Introductionsupporting
confidence: 81%
“…Further, neuroticism is correlated with substance use disorders (Malouff et al 2007), and affect regulation models suggest that individuals high in trait neuroticism may use alcohol to regulate emotions (Cooper et al 1995). In addition to being associated with internalizing and externalizing disorders, negative emotionality explains a substantial proportion of the phenotypic covariation among these disorders (Khan et al 2005; Ellingson et al 2015). Notably, this risk factor resembles the negative valence system, highlighted in the RDoC proposal, which includes subconstructs related to anxiety (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation